Association of KISS1 Gene SNPs (Rs35431622) with Metabolic Parameters in Iraqi Women Polycystic Ovary Syndrome - Bashar Hassan Abood, Rayah Sulaiman Baban, Enas Adnan Abdulrasol (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Polycystic ovarian syndrome (PCOS) is among the most common types of gynecological hormonal abnormalities and metabolic problems that have an impact females throughout adolescence , with a prevalence of 6-10%.Hyperandrogenism, unreliable menstrual periods, and polycystic ovaries are the hallmarks of PCOS. Objectives: The goal of this find out about used to be to analyze the affiliation of kiss1 Gene SNPs (rs35431622) with metabolic Parameters in PCOS . Methodology: a case –control find out about enrolled one hundred sixty members of which eighty female have PCOS and eighty symbolize the manage crew who had-been interestingly healthful. Patients with PCOS had been chosen patients from our health center and the teaching hospital’s gynecology and obstetrics department in Tikrit. Assessment of serum (fasting blood glucose , cholesreol .HDL and triglyceride) was performed using smart 150 full automated clinical chemistry machine .and insulin by ELISA KIT ,HOMA-IR By calculation and the maker company’s provided methodology was followed to extract genomic DNA from whole blood. KISS1 Gene SNPs rs35431622 T>A gene polymorphisms was once detected by using (T-ARMS-PCR) method . Results: The findings indicate, the frequency of the kiss1 gene rs35431622 AT and TT genotypes in PCOS-affected women increased 3.524-fold and 9.633- in comparison to the group of healthy women which have odds ratio; 3.524and 9.633, 95% confidence interval [CI], 1.622-7.657 and 2.916-31.816; P-value ≤0.01**and ≤0.01**) respectively. and The levels of FBS ,Insulin ,HOMA-IR, cholesterol, HDL and triglyceride showed significant difference among PCOS against control group (P≤ 0.0001) . Conclusions: Our find out about suggests a greater awareness of serum (FBS ,Insulin , cholesterol, HDL and triglyceride) seemed in PCOS companies as in contrast with control and also significant difference in the value of HOMA-IR as well, Cases and controls had statistically different frequencies of the identified polymorphisms, and Control 34 had a higher frequency of the homozygous allele (CC) than Cases 12 ., while the frequency of heterozygous allele (AT) were significantly different in cases 51 higher than the controls 41 as well the frequency of mutant allele (tt) were significantly different in cases 17 higher than the controls 5 .The allelic frequency of SNP rs35431622.C/T used.to,be detected extra regularly with significant affiliation infemale with PCOS than in control. Keywords: PCOS, kiss1,(IR)